1.5-multiplicity molecular light scattering in fluids? - Sushko, M.Ya. (Condensed Matter Physics, 2006)
The third-order thermodynamic moment of the density fluctuations is shown to contribute notably to the molecular light scattering in a single-component fluid. The relevant 1.5-scattering is expected to affect the depolarization ratio of the scattered light as the scattering is studied near the critical isochore and for the temperature interval where nonlocal correlation between fluctuations is relatively weak. The experimental data in support of this conclusion are quoted.